Formulation and evaluation of a novel megalomeric microemulsion from tamarind seed xyloglucan-megalosaccharides for improved high-dose quercetin delivery. (April 2023) - Lang, Weeranuch; Mondol, Debashish; Trakooncharoenvit, Aphichat; Tagami, Takayoshi; Okuyama, Masayuki; Hira, Tohru; Sakairi, Nobuo; Kimura, Atsuo
Abstract: Megalomeric microemulsion is a new term referring to lipid-based formulation using amphiphilic megalosaccharide as a coexcipient. Quercetin is a dose-dependent bioactive compound and has promising therapeutic potential, but its low water solubility and permeability restrict its treatment efficacy. We aimed to formulate high-dose quercetin loaded into colloidal micelles by the self-micro emulsifying system (SMES) in combination with Tween 80, isopropyl myristate, and xyloglucan megalosaccharide (X-MS). X-MS is a moderate-size heterologous saccharide obtained from enzymatic cleavage of tamarind seed xyloglucan. X-MSs with an average degree of polymerization of 16 and 56 were investigated to bearing their surface hydrophobic interaction with a fluorescence probe 6-( p -toluidino)-2-naphthalene-6-sulfonate yielded the binding constant values of 127 and 180 M −1, respectively and X-MS itself displayed a slight effect on quercetin binding. However, the implementation of X-MSs toward SMES was highly compatible because X-MS molecules were confined in micellular solutions. Consequently, X-MSs improved the quercetin loading from 1 to 2 to 12.5–17.7 mg/mL based on the composition ratio, X-MS chain lengths, and X-MS concentrations (0.15–3.0%, w/v) and stabilized the quercetin-loaded oil-in-water SMES. The optical appearances were transparent yellow containing uniformly fine droplets with diameters of 11–12 nm. In vitro radical scavenging activity tests with 2, 2-diphenyl-1-picrylhydrazyl showed that the megalomeric microemulsions improved the half-maximal inhibitory concentration (IC50 = 22–24 μg/mL) over that of the X-MS-free microemulsion. This study provided a new approach of liquid supplementation from commercially unavailable-size xyloglucan to be a promising added-value agent for oral uptake of quercetin. Graphical abstract: Image 1 Highlights: X-MS, a shortened xyloglucan, decreased viscosity and maintained hydrophobicity. X-MS participated in Tween 80 micelles, the so-called coemulsifier. The O/W microemulsion coexisting with X-MS DP 16 and 56 formed 11–12-nm droplets. X-MS DP 56 stabilized the dissolved quercetin content up to 17.70 ± 0.40 mg/mL (59 mM).